Defining the Kv2.1-syntaxin molecular interaction identifies a first-in-class small molecule neuroprotectant - Yeh, Chung-Yang; Ye, Zhaofeng; Moutal, Aubin; Gaur, Shivani; Henton, Amanda M; Kouvaros, Stylianos; Saloman, Jami L; Hartnett-Scott, Karen A; Tzounopoulos, Thanos; Khanna, Rajesh; Aizenman, Elias; Camacho, Carlos J (Proceedings of the National Academy of Sciences - PNAS, 2019)
The neuronal cell death-promoting loss of cytoplasmic K following injury is mediated by an increase in Kv2.1 potassium channels in the plasma membrane. This phenomenon relies on Kv2.1 binding to syntaxin 1A via 9 amino acids within the channel intrinsically disordered C terminus. Preventing this interaction with a cell and blood-brain barrier-permeant peptide is neuroprotective in an in vivo stroke model. Here a rational approach was applied to define the key molecular interactions between syntaxin and Kv2.1, some of which are shared with mammalian uncoordinated-18 (munc18). Armed with this information, we found a small molecule Kv2.1-syntaxin-binding inhibitor (cpd5) that improves cortical neuron survival by suppressing SNARE-dependent enhancement of Kv2.1-mediated currents following excitotoxic injury. We validated that cpd5 selectively displaces Kv2.1-syntaxin-binding peptides from syntaxin and, at higher concentrations, munc18, but without affecting either synaptic or neuronal intrinsic properties in brain tissue slices at neuroprotective concentrations. Collectively, our findings provide insight into the role of syntaxin in neuronal cell death and validate an important target for neuroprotection.